Peranan Kebimbangan Karier terhadap Intensi Pindah Jurusan Kuliah pada Mahasiswa - Rhiany Rizqi Fahima; Sari Zakiah Akmal (Psympathic : Jurnal Ilmiah Psikologi, 2018)
Changing academic major could have negative impact on the students, such as increased fees and time for college. The intention of changing academic major is related to the mistake in choosing majors due to student’s career indecision. Career indecision is a situation where an individual is experiencing difficulties, having lack of confident in making decisions or cannot commit to college, career or work to be lived. This study aims to see the role of career indecision on the intention of changing academic major among college students. The method used in this study was associative research. Participants in this study consisted of 175 students between 18 to 26 years old who enrolled in Jakarta-Bogor-Depok-Tangerang-Bekasi, selected with accidental sampling. The result of the study indicates that the career indecision plays a 4.7% share to the intention of changing academic major. Therefore, reducing student’s career indecisions is an alternative solution to decrease the intention of changing academic major.